Parental experiences of rapid exome sequencing in cases with major ultrasound anomalies during pregnancy. (22nd October 2021) - Plantinga, Mirjam; Zwienenberg, Lauren; van Dijk, Eva; Breet, Hanna; Diphoorn, Janouk; El Mecky, Julia; Bouman, Katelijne; Verheij, Joke; Birnie, Erwin; Ranchor, Adelita V.; Corsten‐Janssen, Nicole; van Langen, Irene M.
Abstract: Background: Adding rapid exome sequencing (rES) to conventional genetic tests improves the diagnostic yield of pregnancies showing ultrasound abnormalities but also carries a higher chance of unsolicited findings. We evaluated how rES, including pre‐ and post‐test counseling, was experienced by parents investigating its impact on decision‐making and experienced levels of anxiety. Methods: A mixed‐methods approach was adopted. Participating couples ( n = 46) were asked to fill in two surveys (pre‐test and post‐test counseling) and 11 couples were approached for an additional interview. Results: All couples accepted the rES test‐offer with the most important reason for testing emphasizing their hope of finding an underlying diagnosis that would aid decision‐making. The actual impact on decision‐making was low, however, since most parents decided to terminate the pregnancy based on the major and multiple fetal ultrasound anomalies and did not wait for their rES results. Anxiety was elevated for most participants and decreased over time. Conclusion: Major congenital anomalies detected on ultrasound seem to have more impact on prenatal parental decision‐making and anxiety then the offer and results of rES. However, the impact of rES on reproductive decision‐making and experienced anxiety requires further investigation, especially in pregnancies where less (severe) fetal anomalies are detected on ultrasound. Key points: What is already known about this topic? Adding exome sequencing to conventional prenatal genetic tests improves the diagnostic yield. Prenatal rapid exome sequencing (rES) with a 2‐week turnaround time is feasible. What does this study add? Insight in the impact of rES offer and communication of rES results during pregnancy, including unsolicited findings, on decision‐making and anxiety. Most parents did not wait for their rES results in making decisions regarding their current pregnancy because of the severity of the ultrasound anomalies. Anxiety was elevated for most participants but decreased over time.